Institucionalistas em formação: mapeando a contribuição da EIO em teses e dissertações brasileiras (1995-2022) - Jerônimo, Rodrigo Constantino; Neris Junior, Celso Pereira (História Econômica & História de Empresas, 2025)
This paper examines the prevalence and contribution of Original Institutional Economics (OIE) in Brazilian academic theses and dissertations from 1995 to 2022. A total of 92 documents across 15 fields of knowledge were selected from the Capes Catalog of Theses and Dissertations, filtered by title, keywords, and abstracts. These works were categorized into four approaches: (i) co-applied analysis, where OIE complements other investigations; (ii) theoretical-comparative, contrasting OIE with perspectives like New Institutional Economics and Keynesianism; (iii) theoretical analysis, focused on OIE’s history, methodology, and concepts; and (iv) applied analysis, using OIE to explore specific topics such as labor, environment, and consumption. Employing bibliometric tools and content analysis, the study highlights the prevalence, characteristics, and community formation of OIE scholars in Brazil, addressing the challenges faced in Economics programs.